2011
DOI: 10.1016/j.ejso.2011.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Presence of symptoms and timing of surgery do not affect the prognosis of patients with primary metastatic breast cancer

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. M A N U S C R I P T A C C E P T E D ACCEPTED MANU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Cady et al [23] suggested that most of the survival advantage for patients undergoing surgery is explained by case selection bias, meaning that patients with a good response to initial systemic therapy are also more likely to undergo surgery than those with a poor response. There are numerous studies showing that timing of surgery was no significant prognostic factor for patients with MBC [11,22,24,40]. Similar to the reports in literature we could not find the importance of timing of LRT on survival rates.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Cady et al [23] suggested that most of the survival advantage for patients undergoing surgery is explained by case selection bias, meaning that patients with a good response to initial systemic therapy are also more likely to undergo surgery than those with a poor response. There are numerous studies showing that timing of surgery was no significant prognostic factor for patients with MBC [11,22,24,40]. Similar to the reports in literature we could not find the importance of timing of LRT on survival rates.…”
Section: Discussionsupporting
confidence: 77%
“…LRT in these retrospective series was more frequently used in selected patients with better prognostic profile [7e11, 13,17,22]. These patients were significantly younger, had fewer comorbidities, more often had hormone receptor positive disease, had a lower stage and lower grade tumors, had fewer sites of metastases, less often with visceral metastases, less likely to have symptomatic metastases and more often treated with combined locoregional RT and/or systemic treatment [6e9, 11,13,21,40]. Similar to the literature, the use of LRT was more common in our patients with better prognostic features including T1e2 tumors and solitary metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of surgery in relation to the diagnosis of metastases and use of systemic therapy has not always been specified in the published retrospective literature, although several authors have attempted to address it , with varying conclusions. For the present discussion, the situation of metastatic disease diagnosed in the post‐operative period is not pertinent, since the surgical decision has already been made for these patients.…”
Section: The Retrospective Data On Primary Tumor Resectionmentioning
confidence: 99%
“…Surgical Timing: The timing of surgery in relation to the diagnosis of metastases and use of systemic therapy has not always been specified in the published retrospective literature, although several authors have attempted to address it, 21,29,38,39 with varying conclusions. This is a source of bias in that women who are diagnosed with metastases only after they have undergone surgery for the primary tumor most likely have asymptomatic (and therefore lower-volume) metastases.…”
Section: Potential Biasesmentioning
confidence: 99%